Galz, Please Don't Cry : Pengalaman dan Strategi 14 Cewek Bangkit dari Patah Hati - Asma Nadia (dkk) (Lingkar Pena, 2006)
Galz, Please Don't Cry : Pengalaman dan Strategi 14 Cewek Bangkit dari Patah Hati